2023
DOI: 10.1021/acsmacrolett.2c00706
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Glass Transition Temperature in a Series of Poly(methylene-1,3-cyclopentane-stat-cyclohexane) Statistical Copolymers

Abstract: A systematic investigation of the synthesis and characterization of a new class of amorphous atactic cis, trans poly(methylene-1,3-cyclopentane-stat-cyclohexane) statistical copolymers (I) is reported. Production of different grades of I that vary with respect to the ratio of 5-and 6-membered cycloalkane repeat units was achieved through the living coordinative chain transfer cyclopolymerization of different initial feed ratios of 1,5-hexadiene and 1,6-heptadiene comonomers. It was determined that the glass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Moreover, it is well attested that polymerization of some non-conjugated dienes, such as 1,5-hexadiene (1,5-HD) and 1,7-octadiene (1,7-OD), may also lead to their cyclization, resulting in the insertion of cyclic units and the formation of polymers potentially characterized by both cyclic and unsaturated units . Notably, the homopolymerization of 1,5-HD has been widely investigated through the employment of several catalytic systems. Some of them afford polymers characterized by the presence of vinyl pendant units, , which in some cases have been exploited for post-functionalization reactions. , …”
mentioning
confidence: 99%
“…Moreover, it is well attested that polymerization of some non-conjugated dienes, such as 1,5-hexadiene (1,5-HD) and 1,7-octadiene (1,7-OD), may also lead to their cyclization, resulting in the insertion of cyclic units and the formation of polymers potentially characterized by both cyclic and unsaturated units . Notably, the homopolymerization of 1,5-HD has been widely investigated through the employment of several catalytic systems. Some of them afford polymers characterized by the presence of vinyl pendant units, , which in some cases have been exploited for post-functionalization reactions. , …”
mentioning
confidence: 99%
“…The controllable "precision" polyolefin can help satisfy the technical needs of the future society. In 2023, Sita et al [106] reported that a systematic investigation about the synthesis and characterization a series of amorphous atactic cis, trans poly(methylene-1,3-cyclopentane-stat-cyclohexane) statistical copolymers was carried out innovatively. In this study, the copolymerization of 1,5-hexadiene and 1,6-heptadiene with different initial feed ratios was attempted, in order to produce different grades of products under the catalysis of Scheme 9.…”
mentioning
confidence: 99%
“…This study lays the foundation for DMAB to participate in some specific polymerization reactions about 1, 6-heptadiene. Later, Kaitlyn E. Crawford and Lawrence R. Sita [105] reported another cooperation between DMAB and the transition metal complexes for synthesizing poly ( In 2023, Sita et al [106] reported that a systematic investigation about the synthesis and characterization a series of amorphous atactic cis, trans poly(methylene-1,3-cyclopentane-stat-cyclohexane) statistical copolymers was carried out innovatively. In this study, the copolymerization of 1,5-hexadiene and 1,6-heptadiene with different initial feed ratios was attempted, in order to produce different grades of products under the catalysis of Scheme 10.…”
mentioning
confidence: 99%